Regional Variations in the Permeable Rocks and Porosity of the Water Bearing Formations in Central North Kordofan and West White Nile Areas - El Hadi, M. A.; Gusm Elseed, E. (Gezira Journal of Engineering and Applied Sciences, 2020)
The present study aimed to delineate the regional variations in the permeable rocks and porosity of the water bearing formations in Bara and Kosti basins. The study depended on the determination of the permeable rock ratios and porosity calculation for the lithological samples obtained from borehole pertaining to the study area. Freehand 9.02 software application was used in this study for drawing maps and sections .The lithology indicates vertical and lateral changes in the rocks (sediments) facies forming the subsurface formations. The permeable rocks form the water bearing formations (aquifers) while the impermeable rocks such as clays represent aquiclude layers. The permeable sediments compose of coarse sands and gravels in the western part whereas they consist of medium sands in the eastern part of the study area. The facies description indicates that the ratio (percent) of the permeable rocks decrease from more than 60 % in Bara Basin (Umm Rawaba and El Basheri Sub-basins) in the West to less than 20 % as in Kosti Basin in the East. The porosity values of these rocks range from 17 - 23 % in the western part (Bara Basin) to 28 % in the eastern part. The variation in the rock facies indicates that the sediments composing the water bearing formations were transported from the northwest and southwest directions.